Reconfiguration of knowledge: Academic experience of university reforms at the UTP 1980-1994 - Agudelo Castañeda, Natalia; Correa Ramírez, Jhon Jaime; López García, Edwin Mauricio (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: Explore the change experienced in Colombian higher education since the eighties, specifically through analyzing the practical application of Decree Law 80/1980 at regional and local levels. The main objective is to fill a gap in existing knowledge about the impact of this decree on educational institutions, highlighting its influence on university daily life.